2014
DOI: 10.1016/j.petrol.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Properties of N2- and CO2-foams as a function of pressure

Abstract: The last ~4.5 years have been the most exciting and challenging period in my life so far. I want to use this opportunity to thank at least some of the people who have supported me in one way or another during this period. I wish to express my gratitude to my supervisor Dr. Morten G. Aarra; thank you for sharing your knowledge with me, for your personal encouragement, and for the many good discussions. My co-supervisor, Professor Arne Skauge, deserves a special thank as well; thank you for scientific advice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 230 publications
(739 reference statements)
8
48
1
1
Order By: Relevance
“…De Vries and Wit15 predicted that the water relative permeability at high-quality regime does not monotonically increase with water saturation. In the experiments of Aarra et al 16,. the water relative permeability after foam injection for both N 2 and CO 2 foams experienced a significant reduction with an implication that foam can be used to divert liquid among layers.…”
mentioning
confidence: 93%
“…De Vries and Wit15 predicted that the water relative permeability at high-quality regime does not monotonically increase with water saturation. In the experiments of Aarra et al 16,. the water relative permeability after foam injection for both N 2 and CO 2 foams experienced a significant reduction with an implication that foam can be used to divert liquid among layers.…”
mentioning
confidence: 93%
“…In this study delay in foam strength build-up was observed with non-equilibrated fluids. In addition, visual observations of the foam texture indicated larger bubbles.Compared to N 2 -foams at similar conditions CO 2 -foams were weaker and showed coarser foam structure.Recently in Aarra et al, (2012), we focused on understanding CO 2 -foam properties below and above the critical point of CO 2 (P c ≈ 73.8 bar, T c ≈ 31.0°C). Strong CO 2 -foams were generated when CO 2 was in its gaseous state (30 bar, 50°C).…”
mentioning
confidence: 99%
“…Recently in Aarra et al, (2012), we focused on understanding CO 2 -foam properties below and above the critical point of CO 2 (P c ≈ 73.8 bar, T c ≈ 31.0°C). Strong CO 2 -foams were generated when CO 2 was in its gaseous state (30 bar, 50°C).…”
mentioning
confidence: 99%
“…Foam can affect k rw indirectly through higher trapped gas saturation and reduced water saturation (Aarra et al 2014). Foam can greatly reduce gas mobility in porous media in two ways: reduce gas relative permeability and increase apparent gas viscosity (Falls et al 1988).…”
Section: Introductionmentioning
confidence: 99%